Archeologia klasyczna w poszukiwaniu swej tożsamości. Między przeszłością, teraźniejszą a historią sztuki - Bugaj, Ewa (Folia Praehistorica Posnaniensia, 2018)
The article defines classical archaeology as one of the first and oldest branches of archaeology practised in Europe by stressing that interests in the relics of ancient civilisations have been deeply embedded in the cultural self-identification of various peoples of Europe. The author aims to recognize how the modern world values contribute to interpretation and conservation of the classical past, especially Greek art and architecture, alongside other ancient objects, and how the Western elites treated them in the past centuries. The issue of common roots of classical archaeology and history of art as well as their long-lasting relationships are also thoroughly discussed. Discrepancies between major research procedures of classical archaeology and art history are scrutinized, especially in terms of an arguable irrelevance of modern concept of art in relation to archaeological evidence. The role of museums in relation to art and antiquities trade is also raised. Furthermore, the author discusses classical archaeology within broader issues of contemporary archaeology. It is recognized that classical archaeology has certainly changed by resigning from the previously dominant connoisseur knowledge approach to artefacts, concentrated solely on the works of art often seen as autonomous entities devoid of the context of their production, meaning and perception. Finally, the author defines contemporary classical archaeology as a rapidly changing discipline, reformulating its research agenda and opening up to cooperation with numerous other disciplines. Nevertheless, this should not mean a wholesale rejection of its great legacy of being a history of ancient art. On the contrary, this traditions ought to be redefined and incorporated into contemporary research agenda of the discipline.